PENCIPTAAN BERBAGAI MACAM PRODUK ANYAMAN PANDAN MELALUI TEKNIK ANYAMAN SILANG DAN GEWI - NURFATIHA, Dra. Minarsih, M.Sn., Drs. Erwin A, M.Sn. (Serupa The Journal of Art Education, 2016)
Craftsmen woven Muaro Pingai has produced woven pandanus woven through various techniques especially the technique gewi. Gewi used to generate a new motif on the outskirts of the webbing, ie the structure of the fabric of the basket, the whole product woven from ribbons direction crosswise direction, straight, parallel and also its direction can be broken off to the left and right. The positive impact of these ribbons fault led to a repeated pattern in the edge areas of wicker. The technique is a privilege that is not done by other woven products. This woven craft products inspired by traditional woven mats Muaro Pingai Solok that creates mats through techniques goddess. This goddess technique author joined with cross woven techniques through the method of creation: the preparation, elaboration, synthesis, the realization of the concept and completion. Obtained a result of the creation of a product in the form of a variety of products through technical woven pandanus woven cross and gewi. The results obtained are the product lover table mats, table mats rectangular, women wallets, fashionable bags, tissue boxes, placemats mini and a comb.Keywords: Creation, Products, Woven Pandan, Mechanical Webbing Cross and gewi.